2008
DOI: 10.1002/mds.22027
|View full text |Cite
|
Sign up to set email alerts
|

Striatal and extrastriatal dopamine in the basal ganglia: An overview of its anatomical organization in normal and Parkinsonian brains

Abstract: Degeneration of the nigrostriatal dopaminergic system is the characteristic neuropathological feature of Parkinson's disease and therapy is primarily based on a dopamine replacement strategy. Dopamine has long been recognized to be a key neuromodulator of basal ganglia function, essential for normal motor activity. The recent years have witnessed significant advances in our knowledge of dopamine function in the basal ganglia. Although the striatum remains the main functional target of dopamine, it is now appre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
124
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 162 publications
(131 citation statements)
references
References 153 publications
6
124
0
1
Order By: Relevance
“…To demonstrate the in vivo effect of ghrelin, we utilized the catalepsy model induced by a specific D2 receptor antagonist haloperidol, which has been proven to represent a reliable model for PD and is selectively reversed by clinically effective antiparkinson drugs 45 . Based on the current understanding of neural framework in basal ganglia, degeneration of nigral dopaminergic neurons leads to dopamine depletion in the striatum, resulting in an imbalance of direct and indirect pathway and subsequent motor disorders [46][47][48] . Unilateral microinjection of ghrelin causes the contralateral posturing and anticatalepsy effect, which is likely resulted from enhanced dopamine release induced by ghrelin directly and further activates the pathway of basal ganglia from the ipsilateral cortex.…”
Section: Inhibition Of Voltage-dependent Kcnq/m-currents By Ghrelinmentioning
confidence: 99%
“…To demonstrate the in vivo effect of ghrelin, we utilized the catalepsy model induced by a specific D2 receptor antagonist haloperidol, which has been proven to represent a reliable model for PD and is selectively reversed by clinically effective antiparkinson drugs 45 . Based on the current understanding of neural framework in basal ganglia, degeneration of nigral dopaminergic neurons leads to dopamine depletion in the striatum, resulting in an imbalance of direct and indirect pathway and subsequent motor disorders [46][47][48] . Unilateral microinjection of ghrelin causes the contralateral posturing and anticatalepsy effect, which is likely resulted from enhanced dopamine release induced by ghrelin directly and further activates the pathway of basal ganglia from the ipsilateral cortex.…”
Section: Inhibition Of Voltage-dependent Kcnq/m-currents By Ghrelinmentioning
confidence: 99%
“…84,86 Local interruption of dopamine terminals directed to the STN increase its activity, indicating a direct modulatory effect of dopamine on the STN. 84 We have postulated that early denervation of the STN in PD may act as a compensatory mechanism that maintains the basal ganglia output within normal limits despite a progressive loss of striatal dopamine, 87 thus potentially explaining why clinical features do not emerge until there is a 70 to 80% reduction in striatal dopamine levels.…”
mentioning
confidence: 99%
“…Changes in metabolism in the striatum and thalamus in PD is complex and involves alterations in receptor availability as well as neurotransmitter processing. 11 Studies in rats with 6-hydroxydopamine lesioning have shown a number of changes in metabolism with prolonged high frequency stimulation (HFS), including normalization of COX levels in the substantia nigra with HFS. 12 In the same model, Cytochrome oxidase I mRNA levels in cortical regions have also shown to normalize following HFS.…”
Section: Discussionmentioning
confidence: 99%